Efektivitas Penggunaan Media Crossword Puzzle Berbasis Puzzle Maker terhadap Minat Belajar PAI di SMPN 5 Ajangale - Indriani, Andi; Mujahidin; Wahyuni, Sri; Abubakar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of using crossword puzzle media on students' learning interest in Islamic Religious Education subjects at SMP Negeri 5 Ajangale. This study uses a quantitative approach with a pre-experimental design in the form of one group pretest-posttest design. The population in this study were all students of class VIII of SMP Negeri 5 Ajangale with a total of 30 students. The sampling technique was a saturated sampling technique so that the sample in this study was all students of class VIII totaling 30 students. The research instruments were in the form of questionnaires and observation sheets to determine students' learning interest. Data analysis included descriptive statistics and inferential statistics. The results showed a significant difference in the use of crossword puzzle media on students' learning interest. This is evidenced by the results of the paired samples t-test which showed that the calculated t value> t table (6.799> 2.045) and the significance test α = 0.05 showed a p value <α (0.000 <0.05). This is also proven by the results of observations of students' learning interests after using crossword puzzle media which showed an increase in the average student learning interest from the first meeting to the third meeting. Thus, it can be concluded that the use of crossword puzzle media (crossword puzzles) based on puzzle maker is effective for students' learning interests in Islamic Religious Education (PAI) subjects at SMP Negeri 5 Ajangale.